2018
DOI: 10.1016/j.jbiomech.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element analysis is a valid method for computing joint contact stress in the hip before and after acetabular fracture

Abstract: Evaluation of abnormalities in joint contact stress that develop after inaccurate reduction of an acetabular fracture may provide a potential means for predicting the risk of developing post-traumatic osteoarthritis. Discrete element analysis (DEA) is a computational technique for calculating intra-articular contact stress distributions in a fraction of the time required to obtain the same information using the more commonly employed finite element analysis technique. The goal of this work was to validate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 47 publications
(70 reference statements)
2
33
0
1
Order By: Relevance
“…Peak contact stresses computed using DEA were within an average of 0.5 MPa (range: 0.2-0.8 MPa) of the Tekscan stresses [77]. Correlations between the DEA-computed contact stress distributions and Tekscanmeasured distributions ranged from 0.93-0.99, indicating excellent agreement between the two techniques over the entire contact area [77]. Those results indicated that this custom DEA methodology can accurately predict contact stresses in the hip joint.…”
Section: Previous Work and Rationalementioning
confidence: 68%
See 4 more Smart Citations
“…Peak contact stresses computed using DEA were within an average of 0.5 MPa (range: 0.2-0.8 MPa) of the Tekscan stresses [77]. Correlations between the DEA-computed contact stress distributions and Tekscanmeasured distributions ranged from 0.93-0.99, indicating excellent agreement between the two techniques over the entire contact area [77]. Those results indicated that this custom DEA methodology can accurately predict contact stresses in the hip joint.…”
Section: Previous Work and Rationalementioning
confidence: 68%
“…Contact stresses were physically measured with Tekscan sensors [82] and compared on a point-by-point basis with DEA-calculated stresses. Peak contact stresses computed using DEA were within an average of 0.5 MPa (range: 0.2-0.8 MPa) of the Tekscan stresses [77]. Correlations between the DEA-computed contact stress distributions and Tekscanmeasured distributions ranged from 0.93-0.99, indicating excellent agreement between the two techniques over the entire contact area [77].…”
Section: Previous Work and Rationalementioning
confidence: 80%
See 3 more Smart Citations